Radicalisation in the digital age - Noor Huda Ismail (2025)
Singapore authorities recently arrested three individuals who had been radicalised online by far-right and Islamist extremist religious ideologies. Addressing the growing problem requires a multi-faceted approach, including digital literacy education, early intervention programmes, and community-driven efforts to counter extremist narratives before they take root.